Riesgos físico-mecánicos en la seguridad y salud ocupacional de trabajadores en la purificadora de agua Waterhome Express Canuto - Velásquez Saldarriaga, María Gabriela (2022)
This research was carried out in the water purification plant Waterhome Express Canuto, with the objective of evaluating the physical-mechanical risks in the occupational health and safety of the workers. The diagnosis of the plant was carried out by means of an interview with the administrator, in order to learn about the different processes, regulations and administrative activities. A survey of workers was also used to learn about the incidence of physical-mechanical risks, and a Checklist was applied to determine compliance with current legal regulations, whose percentage of compliance was 46.65%. Physical-mechanical risks were identified using matrices established by the Ministry of Labor Relations, where the physical risks were found: noise, lighting, temperature and humidity. The mechanical risks were as follows: confined space, handling of sharp tools, use of transport, falling objects, obstacles and irregular or slippery floors, maintenance work, heights work, machinery unprotected that present important risk, while confined space, handling of sharp tools, use of transport, falling objects reached the highest weighting called intolerable risk. Finally, an Integral Occupational Risk Prevention Plan was developed, accordance with Ecuadorian regulations, in order to generate safe and healthy work spaces for workers.